Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/biology12070911
|View full text |Cite
|
Sign up to set email alerts
|

Coffee-Associated Endophytes: Plant Growth Promotion and Crop Protection

Abstract: Endophytic microbes are a ubiquitous group of plant-associated communities that colonize the intercellular or intracellular host tissues while providing numerous beneficial effects to the plants. All the plant species are thought to be associated with endophytes, majorly constituted with bacteria and fungi. During the last two decades, there has been a considerable movement toward the study of endophytes associated with coffee plants. In this review, the main consideration is given to address the coffee-associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 148 publications
(186 reference statements)
0
0
0
2
Order By: Relevance
“…Water absorption, resistance to adverse conditions, and the ability to inhibit pathogenic fungi could prevent soil diseases and directly affect coffee productivity. The selective suppression of pathogens the microbial communities could contribute to the overall health of the plants and, therefore, to an increase in the productivity of coffee beans (Souza et al, 2015;Glick, 2012;Abdelaal et al al., 2021;Urgiles-Gómez et al, 2021;Asad et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Water absorption, resistance to adverse conditions, and the ability to inhibit pathogenic fungi could prevent soil diseases and directly affect coffee productivity. The selective suppression of pathogens the microbial communities could contribute to the overall health of the plants and, therefore, to an increase in the productivity of coffee beans (Souza et al, 2015;Glick, 2012;Abdelaal et al al., 2021;Urgiles-Gómez et al, 2021;Asad et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These isolates belong to the phylum Ascomycota, with a predominant presence of two classes Sordariomycetes and Dothideomycetes. The Phylum Ascomycota, particularly the Sordariomycetes and Dothideomycetes classes, is widely recognized as the most common representative of endophytic fungi communities in tea [32] and all types of plants, such as Mangrove (Rhizohora mucronate [12]), coffee trees (Coffea arabica L. and Coffea canephora L. [44]), Vinca rosea (Catharanthus riseos [45]), Orchid (Guarianthe skinneri [46]), and beach vitex (Vitex rotundifolia [47]).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [20] suggested that the fungal endophytes in their study assisted medical plants under abiotic stress conditions by producing and accumulating some highly coveted secondary metabolites. Since, secondary metabolite production in fungi might depend on their host species and on environmental conditions [9,15,44], there is a possibility that an imbalance in the conventional system affects the secondary metabolite production of fungal endophytes. All the fungal endophytes that demonstrated antifungal activity were obtained from host plants in the conventional system.…”
Section: Discussionmentioning
confidence: 99%
“…Sistem budidaya kopi di lahan Agroforestry seringkali ditemukan terintegrasi dengan sistem pertanian lain yaitu tanaman lain yang ditanam bersamaan dengan komoditas pertanian kopi. Metode tradisional yang masih dilakukan oleh petani kopi adalah masih penggunaan pestisida dan pupuk sintetik untuk menyelesaikan permasalahan dalam budidaya tanaman kopi namun penggunaannya dapat merugikan bagi mikroba dan menyebabkan pencemaran tanah ( Narango et al, 2019;Siles et al, 2022;Asad et al, 2023;Purba et al, 2023).…”
unclassified
“…Oleh karena itu, dibutuhkan pertanian yang berkelanjutan supaya dapat memenuhi kebutuhan dan melestarikan sumber daya alam. Upaya yang terus dilakukan adalah dengan meminimalkan penggunaan pupuk hayati yang mendukung pertanian berkelanjutan (Duguma et al, 2019;Siles et al, 2022;Adeleke et al, 2021;Asad et al, 2023;Purba et al, 2023;) Bakteri endofit diketahui mampu menghasilkan IAA (Indole acetic acid) yaitu fitohormon yang dapat mempercepat pertumbuhan tanaman (Purba et al, 2023). Penelitian (Pratiwi et al, 2020) memperoleh Bacillus cereus ATCC 14579, yaitu bakteri endofit dari akar tanaman kopi Robusta dan Kopi Arabika yang memiliki potensi penghasil hormon IAA (indole acetic acid) untuk memicu pertumbuhan tanaman kopi.…”
unclassified